HIF-hypoxia signaling in skeletal muscle physiology and fibrosis - Valle-Tenney, Roger; Rebolledo, Daniela; Jose Acuna, Maria; Brandan, Enrique (My University, 2020)
Hypoxia refers to the decrease in oxygen tension in the tissues, and the central effector of the hypoxic response is the transcription factor Hypoxia-Inducible Factor alpha (HIF1-alpha). Transient hypoxia in acute events, such as exercising or regeneration after damage, play an important role in skeletal muscle physiology and homeostasis. However, sustained activation of hypoxic signaling is a feature of skeletal muscle injury and disease, which can be a consequence of chronic damage but can also increase the severity of the pathology and worsen its outcome. Here, we review evidence that supports the idea that hypoxia and HIF-1 alpha can contribute to the establishment of fibrosis in skeletal muscle through its crosstalk with other profibrotic factors, such as Transforming growth factor beta (TGF-beta), the induction of profibrotic cytokines expression, as is the case of Connective Tissue Growth Factor (CTGF/CCN2), or being the target of the Renin-angiotensin system (RAS).
Keywords: muscle fibrosis; hypoxia; vasculature; ccn2; ctgf; renin-angiotensin system